Rapid deformation of IPMC under a high electrical pulse stimulus inspired by action potential. (14th December 2018) - Zhu, Zicai; Bian, Changsheng; Ru, Jie; Bai, Wanfa; Chen, Hualing
Abstract: Slow deformation seriously restrains application development of IPMC actuator, especially for thick and ionic liquid-based IPMC. Inspired by the action potential of muscle cell, this letter proposes a concept of high electrical pulse stimulus to accelerate IPMC deformation. By analyzing the dynamic process of voltage drop at the electrode-polymer interface, high voltage pulse is proved theoretically to be safe for IPMC in a short time. After charging the electrical double layer at the interface, the voltage pulse should be reduced to a safe level before electrochemical reactions. In our experiments, applying various high voltage pulses to a thick IPMC, the deformation can be sped up a few hundred times at most without any electrolysis damage. The results strongly support the practicability of the impulsive driving method.